2008
DOI: 10.1007/s11154-008-9077-1
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in the adolescent athlete

Abstract: Adolescence is a critical time for bone mass accrual, and increases in bone mass through puberty are dependent on rising levels of gonadal steroids, growth hormone and insulin like growth factor-1. Many high school girls are involved in athletic activities, and as many as 23.5% of adolescent athletes have been reported to develop amenorrhea. This review focuses on (1) factors that determine which athletes are likely to develop amenorrhea, such as a negative energy balance state, low levels of leptin and high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
1
34
0
2
Order By: Relevance
“…60 In cell cultures, ghrelin exerted proliferative effects on osteoblasts, whereas studies on animal models indicated that leptin decreases bone mass. 61 Christo et al reported higher ghrelin and lower leptin levels in amenorrheic adolescent athletes compared to eumenorrheic athletes and sedentary controls. 62 This study showed bone age, lean mass, IGF-1 and estradiol, but not ghrelin and leptin, as important positive predictors of bone mass parameters.…”
Section: Effects On Bonesmentioning
confidence: 97%
“…60 In cell cultures, ghrelin exerted proliferative effects on osteoblasts, whereas studies on animal models indicated that leptin decreases bone mass. 61 Christo et al reported higher ghrelin and lower leptin levels in amenorrheic adolescent athletes compared to eumenorrheic athletes and sedentary controls. 62 This study showed bone age, lean mass, IGF-1 and estradiol, but not ghrelin and leptin, as important positive predictors of bone mass parameters.…”
Section: Effects On Bonesmentioning
confidence: 97%
“…In humans, bone mineral accrual is maximal in adolescence and 90% of peak bone mass is achieved by 18 years of age [1]. Low bone mass increases the risk of fracture [2], and for every standard deviation of decrease in bone mineral density (BMD), fracture risk increases two to three times.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches docu men ted the influence of hypoes tro genism on the increase of the level of bone resorption markers, reduction of BMD and the consequential occurrence of osteo po rosis in postmenopausal women (22)(23)(24). However, very few researches have targeted the dynamics of bone metabolism markers in sports women with menstrual dysfunctions or secon dary osteoporosis (25)(26)(27)(28). Since estrogen supp resses remodeling of the bone and acts antire sor p tively, reduction of its level may turn the bone meta bolism in the resorption direction, with a prevalence of its markers (4,28).…”
Section: Discussionmentioning
confidence: 99%
“…However, very few researches have targeted the dynamics of bone metabolism markers in sports women with menstrual dysfunctions or secon dary osteoporosis (25)(26)(27)(28). Since estrogen supp resses remodeling of the bone and acts antire sor p tively, reduction of its level may turn the bone meta bolism in the resorption direction, with a prevalence of its markers (4,28). Values of bone metabolism markers in our study showed a statistically significant difference in the level of bone resorption marker, b-CrossLaps, between the groups of amenorrheic and oligomenorrheic sports women in comparison to eumenorrheic women, both sportswomen and those in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation